RANCANG BANGUN MESIN PENCUCI RUMPUT LAUT BERBASIS TEKNOLOGI HYBRID - Wiliandi Setiawan; Indra Jaya; Totok Hestirianoto (Fakultas Perikanan dan Ilmu Kelautan, 2011)
Seaweed has a high economic value in terms of its considerable use in various industries of sweets, cosmetics, ice cream, flavourings, bakery, sauce, silk, meat/fishery canning, medicine and iron-rod welding. In 2005, Indonesia has declared that seaweed as one of the leading commodities to be prioritized and revitalized. To produce quality of industrial-scale seaweed has necessary a serious handling, start from harvesting process, uploading, washing, drying, up to manufacturing caraggenan.This study has tried to produce a seaweed washing machine that capable to improve the quality of the seaweed in the washing process. This washing machine is based on hybrid technology that can be operated using energy from pedal-powered and electrical-powered generated from solar panels.The washing machine resemble three-wheeled transport vehicle using pedal-powered for mobility. Activity of seaweed washing process using plastic drum that rotated. There are two different size of plastic drum used in washing machine, the bigger size for static water storage containers and the little one for dynamic (rotation) using pedal-powered or electrical motor.The rolled chain transmission that connected with integrated toothed gear is used to ratate a dynamic drum. The different between pedal-powered and electrical-motor powered lies in process to rotated dynamic drum. Pedal-powered use manpower to rotated dynamic drum but electrical motor powered from electrical that generated from solar panel. Washing machine with pedal-powered similar like pedal powered that contained in bicycle. Solar panel systems which is the source energy for generated electrical motor consists of solar panel itself, controller, battery and DC to AC converter. Overall the machine has works well butt need improvement in terms of manueverability.